2009
DOI: 10.1103/physrevc.79.015208
|View full text |Cite
|
Sign up to set email alerts
|

Near-threshold production of theηmeson via the quasifreepnpnηreaction

Abstract: Total cross sections for the quasifree pn → pnη reaction in the range from the kinematical threshold up to 20 MeV excess energy have been determined. At threshold they exceed corresponding cross sections for the pp → ppη reaction by a factor of about 3 in contrast to the factor of 6 established for higher excess energies. To large extent, the observed decrease of the ratio σ (pn → pnη)/σ (pp → ppη) toward threshold may be assigned to the different energy dependence of the proton-proton and proton-neutron final… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…The near-threshold η meson production in nucleonnucleon collisions has been investigated extensively in the CELSIUS, COSY and SATURNE facilities. The results determined by different experiments for the total (Bergdolt et al, 1993;Calen et al, 1996;Chiavassa et al, 1994;Hibou et al, 1998;Moskal et al, , 2010Smyrski et al, 2000) and differential (Abdel-Bary et al, 2003;Moskal et al, , 2010Petren et al, 2010) crosssections for the pp → ppη and for the quasi-free pn → pnη reactions (Calen et al, 1996(Calen et al, , 1998Moskal et al, 2009) are consistent within the estimated uncertainties. In the different experiments η mesons could be produced up to excess energy E of 92 MeV at CELSIUS, 502 MeV at COSY and 593 MeV at SATURNE.…”
Section: η-And η -Nucleon Interactionssupporting
confidence: 68%
See 2 more Smart Citations
“…The near-threshold η meson production in nucleonnucleon collisions has been investigated extensively in the CELSIUS, COSY and SATURNE facilities. The results determined by different experiments for the total (Bergdolt et al, 1993;Calen et al, 1996;Chiavassa et al, 1994;Hibou et al, 1998;Moskal et al, , 2010Smyrski et al, 2000) and differential (Abdel-Bary et al, 2003;Moskal et al, , 2010Petren et al, 2010) crosssections for the pp → ppη and for the quasi-free pn → pnη reactions (Calen et al, 1996(Calen et al, , 1998Moskal et al, 2009) are consistent within the estimated uncertainties. In the different experiments η mesons could be produced up to excess energy E of 92 MeV at CELSIUS, 502 MeV at COSY and 593 MeV at SATURNE.…”
Section: η-And η -Nucleon Interactionssupporting
confidence: 68%
“…Measurements of the isospin dependence of η meson production in proton-nucleon collisions revealed that the total cross-section for the quasi-free pn → pnη reaction exceeds the corresponding cross section for pp → ppη by a factor of about three at threshold and by factor of six at higher excess energies between about 25 and 100 MeV (Calen et al, 1998;Moskal et al, 2009). The strong isospin dependence tells us there must be a significant isovector exchange contribution at work in the protonnucleon collisions.…”
Section: η-And η -Nucleon Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…More constraints to the theoretical models [5,6,[20][21][22][23][24][25] have been deduced from the determination of the dependence on the isospin of the colliding nucleons [26]. The experiments performed by the WASA/PROMICE collaboration [26] revealed a strong isospin dependence confirmed at threshold by the COSY-11 group [27,28]. All together, the confrontation of predictions based upon different scenarios, involving exchanges of various mesons, with the so far determined unpolarised observables and with the first results on the analysing power indicate the dominance of π exchange in the production process [3].…”
Section: Dynamics Of the Pp → Ppη Reactionmentioning
confidence: 99%
“…Previous studies by the CELSIUS [10][11][12][13], COSY [14][15][16][17][18], and SATURNE [19][20][21] experiments of the total and differential cross sections for η meson production in pp and pn collisions revealed that the η meson is predominantly produced via the excitation of one of the nucleons to the S 11 current via exchange of virtual mesons with the subsequent decay into the proton-η pair. This conclusion was obtained from the observation of a large η production cross section relative to the η 0 meson production and the isotropic angular distribution of the η mesons in the center-of-mass (c.m.)…”
mentioning
confidence: 99%